Instrumental preparation for the experimental investigation of air-impulse methods of forming - D. M. Kukuj; D. M. Golub (Литьë и металлургия)
There are given the list of the main physical magnitudes, affecting on the quality of sand-clay mode, received at air- impulse compression, and also the necessary kit for their measuring.